Echocardiographic reference ranges for normal non-invasive myocardial work indices: results from the EACVI NORRE study - Manganaro, Roberta; Marchetta, Stella; Dulgheru, Raluca; Ilardi, Federica; Sugimoto, Tadafumi; Robinet, Sébastien; Cimino, Sara; Go, Yun Yun; Bernard, Anne; Kacharava, George; Athanassopoulos, George D; Barone, Daniele; et al. (European heart journal cardiovascular imaging, 2019)
To obtain the normal ranges for 2D echocardiographic (2DE) indices of myocardial work (MW) from a large group of healthy volunteers over a wide range of ages and gender. A total of 226 (85 men, mean age: 45 ± 13 years) healthy subjects were enrolled at 22 collaborating institutions of the Normal Reference Ranges for Echocardiography (NORRE) study. Global work index (GWI), global constructive work (GCW), global work waste (GWW), and global work efficiency (GWE) were estimated from left ventricle (LV) pressure-strain loops. Peak LV systolic pressure was non-invasively derived from brachial artery cuff pressure. The lowest values of MW indices in men and women were 1270 mmHg% and 1310 mmHg% for GWI, 1650 mmHg% and 1544 mmHg% for GCW, and 90% and 91% for GWE, respectively. The highest value for GWW was 238 mmHg% in men and 239 mmHg% in women. Men had significant lower values of GWE and higher values of GWW. GWI and GCW significantly increased with age in women. The NORRE study provides useful 2DE reference ranges for novel indices of non-invasive MW.